Modern Nigeria - Arnold, Guy. (London : Longman, 1977)
This comprehensive survey of Nigeria's recent past, including on-the-spot coverage of the 1975 coup, equips the reader with a sound coverage and understanding of Nigeria's development efforts.
includes appendixes
Includes bibliographical references and index.
ijb 16/01/2019
Loans
Keywords: Nigeria---History; History; Nigeria